Vloga merjenja prevodnosti kože za prepoznavo bolečinskega odziva pri novorojenčkih - Prusnik, Joanna (Zdravniški vestnik, 2023)
Background: Painful experiences of the newborn lead to short and long-term consequences making prompt recognition and treatment of pain crucial. Skin Conductance Algesimeter (SCA) is a new, non-invasive, objective method to measure pain resulting from an autonomic response to stress or nociceptive stimuli. These activate the sympathetic nervous sys - tem leading to increased perspiration of the palms and soles which in turn amplifies skin conductance. We aimed to define the clinical significance of nociception control by measuring skin conductance in newborns exposed to painful stimuli and assessing its potential introduction into clinical practice. Methods: The sample of our prospective study consisted of 35 newborns treated at the Department of Neonatology, Paediatric Division of the University Medical Centre Ljubljana, from 1 October 2020 to 30 April 2021. Physiological- parameter measurements, pain assessment using the NIPS and NPASS scales, and skin conductance measurements were performed 5 minutes before, during, and 5 minutes after the nociceptive stimulus. The statistical analysis was carried out using Friedman’s two-way analysis of variance by ranks with post hoc tests, Mann-Whitney U test, and logistic regression. Results: Skin conductance changed significantly during painful stimulus in comparison with measurements before or after painful stimulus (p=0.000, p=0.000), as did heart rate (p=0.000, p=0.000), oxygen haemoglobin saturation (p=0.021, p=0.012) and NIPS (p=0.000, p=0.00) and NPASS scores (p=0.000, p=0.000). The respiratory rate did not change significantly throughout the experiment (p=0.098). The NPASS scale had the largest area under the ROC curve at 0.987 95% CI 0.969, 1 and the smallest number of peaks per second at 0.869 95% CI 0.780, 0.958. Conclusions: Skin conductance changes correlate well with changes in physiological parameters and pain scale scores. Methods of measuring pain response predict the pain stimulus with varying degrees of accuracy.
Keywords: bolečinski dražljaj; newborn; nocicepcija; nociception; novorojenček; noxious stimulus